Preparation method of Pd-coated NaYF4Yb3+Er3 +-coated MOF composite material

By doping nanopd and NaYF4:Yb3+/Er3+ into the zeolite-like imidazole skeleton ZIF-8, forming a Pd/NaYF4:Yb3+/Er3+-MOF composite material, it is solved that it is difficult to simultaneously coat nanopalladium and upconversion in the prior art. The problem of materials has achieved stable composite and versatility of materials, and has broadened its application in the fields of catalysis, phototherapy, etc.

CN119114060APending Publication Date: 2024-12-13HEFEI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310896026.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to prepare MOFs materials that coat nanopalladium and upconversion materials simultaneously, and fail to fully combine the advantages of both, limiting their application in the fields of catalysis, phototherapy, etc.

Method used

By doping nano Pd and NaYF4:Yb3+/Er3+ into the zeolite-like imidazole framework ZIF-8, a Pd/NaYF4:Yb3+/Er3+-MOF composite material is formed, and the stable composite of the two materials is achieved and the limitations of single material composite is broken.

Benefits of technology

The stable composite of nano Pd and NaYF4:Yb3+/Er3+ is achieved, which broadens the application range of materials, improves catalytic, phototherapy performance and degradation capabilities, and provides the possibility of multifunctional composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114060A_ABST
    Figure CN119114060A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Pd (at) NaYF4Yb < 3 + > Er < 3 + > (at) MOF composite material in the technical field of composite materials, and the preparation method of the Pd (at) NaYF4Yb < 3 + > Er < 3 + > (at) MOF composite material comprises the following steps: synthesis of an up-conversion nano fluorescent material: weighing 0.473 g of analytically pure yttrium chloride hexahydrate, 0.155 g of ytterbium chloride hexahydrate and 0.0153 g of erbium chloride hexahydrate one by one, putting the materials into a 50 mL beaker, weighing 10 mL of ethylene glycol, pouring the ethylene glycol into the beaker, and stirring the materials at the temperature of 50 DEG C for 20 minutes; the preparation method comprises the following steps: adding a zeolite-like imidazole framework ZIF-8 into a glass rod for stirring and dissolving, weighing 0.5 g of xylitol, adding one piece of xylitol for dissolving, performing auxiliary acceleration in a heating jacket until the medicine is completely dissolved, weighing 0.168 g of sodium fluoride for dissolving in 10mL of ethylene glycol, and placing in a 25mL beaker. According to the invention, nano Pd and NaYF4: Yb < 3 + > / Er < 3 + > are doped into the zeolite-like imidazole framework ZIF-8 to obtain the stable compound Pd / NaYF4: Yb < 3 + > / Er < 3 + >-MOF integrating two materials. Two different materials with different characteristics are doped into the same system at the same time, the limitation of compounding of a single material is broken through, and possibility is provided for simultaneous compounding of three or more materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and specifically to a Pd@NaYF4Yb 3+ Er 3+ @Preparation method of MOF composite material. Background Art

[0002] With the further development of modern society, people's demand for multifunctional composite materials is growing day by day. However, the properties of a single substance are limited and there will always be different shortcomings, which restricts its use in various application fields. Therefore, how to compound two or even more different substances on a microscopic scale or assist each other to synthesize composite materials with higher added value has become an urgent problem that researchers need to solve. Among them, the experimental method of using porous materials to load functional material particles to form a core-shell structure has attracted much attention. As early as the 1980s, some scholars discovered that some heterogeneous composite particles or sandwich particles showed a high activity state that single-phase particles did not have during the experiment, and even showed new properties under certain specific experimental conditions. With the in-depth study of scholars on composite particles with multi-layer structures, the term "core-shell structure" has gradually become known to people.

[0003] The existing traditional porous materials that can be used as carriers are mainly composed of molecular sieves, porous oxides, porous organic polymers, etc., but these have significant defects and cannot be widely used. For example, the modification methods are limited and functionalization is difficult, the pore size and structure are fixed and not conducive to regulation, and the range of load materials available is relatively narrow. In the 1990s, Yaghi et al. prepared porous skeleton structure MOFs by complexing metal particle cores with organic ligands. This pioneering material has frequently appeared in chemical research in various fields. Compared with traditional porous load materials, MOFs materials have some obvious application advantages, such as a wide range of metals and ligands required to construct the framework, easy modification treatment, which is conducive to further development of functional optimization, and a richer pore structure and a large specific surface area for the coating and growth of other functional particles.

[0004] Core-shell structured particles generally use nanoscale particles as the core, and materials of different compositions, sizes, and structures are grown and coated on the surface of the core particles in one or more layers through chemical reactions, thus forming a multifunctional composite material. The composite of multiple materials may lead to the superposition of the excellent properties of single-component materials, and may also have excellent properties different from those of single-component materials. Therefore, in recent years, core-shell particles have been widely used in materials chemistry, biology, tumor treatment, catalytic reactions and other fields.

[0005] At present, metal organic framework materials loaded with nano-palladium as industrial catalysts have the advantages of mild reaction conditions, no need for nitrogen protection and ligand addition, and excellent yield. For tumor treatment, it can effectively cause cell damage and apoptotic cell death under light. Loading upconversion materials can broaden the carrier's absorption spectrum range and significantly improve the photocatalytic performance and degradation ability. MOF materials represented by ZIFs have good thermal stability and chemical stability, regular pores, large specific surface area and pore volume, and can be used in a variety of fields. Coating only one functional material is slightly single, so it is of great significance to study and prepare MOFs materials that simultaneously coat nano-palladium and upconversion materials and combine the advantages of both new composite materials. Summary of the invention

[0006] The purpose of the present invention is to provide a Pd@NaYF4Yb 3+ Er 3+ @The preparation method of MOF composite material is to solve the problem proposed in the above background technology of studying and preparing MOFs materials that simultaneously coat nano-palladium and up-conversion materials and combine the advantages of both new composite materials.

[0007] To achieve the above object, the present invention provides the following technical solution: a Pd@NaYF4Yb 3+ Er 3+ @MOF composite material preparation method, the Pd@NaYF4Yb 3+ Er 3+ The preparation method of @MOF composite material includes the following steps:

[0008] S1: Synthesis of upconversion nano fluorescent materials: weigh 0.473g of analytically pure yttrium chloride hexahydrate, 0.155g of ytterbium chloride hexahydrate, and 0.0153g of erbium chloride hexahydrate one by one and place them in a 50mL beaker, measure 10mL of ethylene glycol and pour it into the above beaker, stir with a glass rod to dissolve, weigh 0.5g of xylitol and add it to dissolve, and assist in accelerating in a heating mantle until all the drugs are dissolved, weigh 0.168g of sodium fluoride and dissolve it in 10mL of ethylene glycol and place it in a 25mL beaker, stir with a glass rod until it is completely dissolved, and then add it dropwise to the above 50mL beaker, then pour all the solution into a high-pressure reactor and place it in a muffle furnace under constant temperature conditions, let it stand for a period of time, cool it naturally, and then take it out, centrifuge the solution at high speed and pour out the supernatant, retain the bottom upconversion nano fluorescent material precipitate for standby use;

[0009] S2: Synthesis of upconversion nano fluorescent composite material MOF: Weigh 0.0792g polyvinyl pyrrolidone and completely dissolve it in 10mL methanol, and place it in a sealed plastic bottle. Take the upconversion fluorescent material in step S1 and wash it twice with methanol to wash away the excess reactants, pour it into a plastic bottle, seal it, and stir it for 12h at room temperature as solution C for standby use. Weigh 0.6568g analytical pure 2-methylimidazole and completely dissolve it in 9mL methanol, and place it in a 25mL beaker as solution A for standby use. Weigh 0.2916g zinc nitrate and completely dissolve it in 9mL methanol, and place it in a 50mL beaker as solution B for standby use.

[0010] Pour solution C into solution B and mix well, place solutions A and B in a refrigerator for 15 minutes and then take them out, pour solution A into solution B and mix well, then refrigerate in an ice bath at 0°C for 24 hours, take them out and centrifuge them at 12000r / min for 15 minutes, pour out the supernatant, and keep the bottom upconversion nano fluorescent composite material MOF material precipitate for later use;

[0011] S3: Synthesis of upconversion nanofluorescent and nano-palladium composite MOF: Synthesis of upconversion nanofluorescent and nano-palladium composite MOF is synthesized by methanol system or by water system

[0012] The methanol system synthesis includes the following steps

[0013] Weigh 0.01g of potassium chloropalladate, stir thoroughly and completely dissolve in 30mL of methanol, and place in a sealed plastic bottle. Take the upconversion fluorescent composite material MOF in the previous step and wash it twice with methanol to wash away excess reactants, pour it into the methanol solution of potassium chloropalladate, seal it, stir it at room temperature for 24h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom precipitate for later use. Weigh 0.01g of sodium borohydride and dissolve it in 10mL of methanol at 0℃ and place it in a sealed plastic bottle for later use. Wash the bottom precipitate with methanol three times, ultrasonically disperse it into 10mL of methanol, and then drop it into the methanol solution of sodium borohydride drop by drop, seal it, stir it at room temperature for 2h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nano-fluorescence and nano-palladium composite material MOF material precipitate;

[0014] The water system synthesis includes the following steps

[0015] Weigh 0.0326g of potassium chloropalladate and completely dissolve it in 10mL of distilled water, place it in a sealed plastic bottle, take the upconversion fluorescent composite material MOF in the previous step, wash it twice with distilled water to wash away excess reactants, pour it into the aqueous solution of potassium chloropalladate, seal it, stir it at room temperature for 12h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, retain the bottom precipitate, disperse it in 10mL of distilled water, place it in a 100mL three-necked flask, oil bath it at 80℃ and keep it stable for 10min, weigh 0.17612g of ascorbic acid and completely dissolve it in 10mL of distilled water, drop it into the above three-necked flask stabilized at 80℃, stir it for 2h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nanofluorescent and nanopalladium composite material MOF material precipitate.

[0016] Preferably, the temperature of the heating jacket in step S1 is 80°C.

[0017] Preferably, the constant temperature in step S1 is 200°C.

[0018] Preferably, in step S1, the solution is allowed to stand in the muffle furnace for 2 hours.

[0019] Preferably, the centrifugal speed of the solution in step S1 is 12000 r / min, and the centrifugal time is 15 min.

[0020] Preferably, the A and B solutions in step S2 are placed in a refrigerator at 0°C.

[0021] Compared with the prior art, the invention has the following beneficial effects: 3+ Er 3+ @MOF composite material preparation method, by mixing nano Pd with NaYF4:Yb 3+ / Er 3+ Pd / NaYF4:Yb is doped into the zeolite imidazole framework ZIF-8 to obtain a stable composite of the two materials. 3+ / Er 3+ -MOF. Two different materials with different properties are doped into the same system at the same time, breaking through the limitations of single material compounding and providing the possibility of realizing the simultaneous compounding of three or more materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The NaYF4:Yb 3+ / Er 3+ -TEM schematic diagram of MOF sample;

[0023] Figure 2 The NaYF4:Yb 3+ / Er 3+ -Schematic diagram of EDS of MOF sample;

[0024] Figure 3 The Pb / NaYF4:Yb 3+ / Er 3+ -TEM schematic diagram of MOF sample;

[0025] Figure 4 Pb / NaYF4:Yb in the methanol system of the present invention 3+ / Er 3+ -Schematic diagram of TEM image of MOF sample;

[0026] Figure 5 The present invention Pb / NaYF4:Yb 3+ / Er 3+ -Schematic diagram of EDS of MOF sample;

[0027] Figure 6 The present invention Pb / NaYF4:Yb 3+ / Er 3+ -Schematic diagram of MOF samples to be tested;

[0028] Figure 7 The present invention Pb / NaYF4:Yb 3+ / Er 3+ -Schematic diagram of the distribution of main elements in MOF;

[0029] Figure 8 The NaYF4:Yb 3+ / Er 3+ - Fluorescence spectrum of MOF;

[0030] Fig. 9 The present invention Pd / NaYF4:Yb 3+ / Er 3+ - Fluorescence spectrum of MOF;

[0031] Fig.10 The present invention Pd / NaYF4:Yb 3+ / Er 3+ -XRD pattern of MOF. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention provides a Pd@NaYF4Yb 3+ Er 3+ @MOF composite material preparation method, by mixing nano Pd with NaYF4:Yb 3+ / Er 3+ Pd / NaYF4:Yb is doped into the zeolite imidazole framework ZIF-8 to obtain a stable composite of the two materials. 3+ / Er 3+ -MOF. Two different materials with different properties are doped into the same system at the same time, breaking through the limitation of single material composite and providing the possibility of realizing the composite of three or more materials at the same time. 3+ Er 3+ The preparation method of @MOF composite material includes the following steps:

[0034] S1: Synthesis of upconversion nano fluorescent materials: weigh 0.473g of analytical pure yttrium chloride hexahydrate, 0.155g of ytterbium chloride hexahydrate, and 0.0153g of erbium chloride hexahydrate one by one and place them in a 50mL beaker, measure 10mL of ethylene glycol and pour it into the above beaker, stir with a glass rod to dissolve, weigh 0.5g of xylitol and add it to dissolve, which can be accelerated in a heating mantle at 80°C until the drugs are completely dissolved, weigh 0.168g of sodium fluoride and dissolve it in 10mL of ethylene glycol and place it in a 25mL beaker, stir with a glass rod until it is completely dissolved, and then add it dropwise to the above 50mL beaker, then pour all the solution into a high-pressure reactor and place it in a muffle furnace at a constant temperature of 200°C for 2h, then cool it naturally and take it out, centrifuge the solution at 12000r / min for 15min, pour out the upper clear liquid, and retain the bottom upconversion nano fluorescent material precipitate for standby use;

[0035] S2: Synthesis of upconversion nano fluorescent composite material MOF: Weigh 0.0792g polyvinyl pyrrolidone and completely dissolve it in 10mL methanol, place it in a sealed plastic bottle, take the upconversion fluorescent material in the previous step and wash it twice with methanol to wash away the excess reactants, pour it into a plastic bottle, seal it, and stir it at room temperature for 12h as solution C for standby use, weigh 0.6568g analytical pure 2-methylimidazole and completely dissolve it in 9mL methanol, place it in a 25mL beaker as solution A for standby use, weigh 0.2916g zinc nitrate and completely dissolve it in 9mL methanol, place it in a 50mL beaker as solution B for standby use;

[0036] Pour solution C into solution B and mix well, place solutions A and B in a refrigerator at 0°C for 15 minutes and then take them out, pour solution A into solution B and mix well, refrigerate in an ice bath at 0°C for 24 hours, take them out and centrifuge at 12000r / min for 15 minutes, pour out the supernatant, and keep the bottom upconversion nano fluorescent composite material MOF material precipitate for later use;

[0037] S3: Synthesis of upconversion nanofluorescent and nanopalladium composite MOF: Synthesis of upconversion nanofluorescent and nanopalladium composite MOF is synthesized by methanol system or by water system.

[0038] The methanol system synthesis includes the following steps

[0039] Weigh 0.01g of potassium chloropalladate, stir thoroughly and completely dissolve in 30mL of methanol, and place in a sealed plastic bottle. Take the upconversion fluorescent composite material MOF in the previous step and wash it twice with methanol to wash away excess reactants, pour it into the methanol solution of potassium chloropalladate, seal it, stir it at room temperature for 24h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom precipitate for later use. Weigh 0.01g of sodium borohydride and dissolve it in 10mL of methanol at 0℃ and place it in a sealed plastic bottle for later use. Wash the bottom precipitate with methanol three times, ultrasonically disperse it into 10mL of methanol, and then drop it into the methanol solution of sodium borohydride drop by drop, seal it, stir it at room temperature for 2h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nano-fluorescence and nano-palladium composite material MOF material precipitate;

[0040] The water system synthesis includes the following steps

[0041] Weigh 0.0326g of potassium chloropalladate and completely dissolve it in 10mL of distilled water, place it in a sealed plastic bottle, take the upconversion fluorescent composite material MOF in the previous step, wash it twice with distilled water to wash away excess reactants, pour it into the aqueous solution of potassium chloropalladate, seal it, stir it at room temperature for 12h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, retain the bottom precipitate, disperse it in 10mL of distilled water, place it in a 100mL three-necked flask, oil bath it at 80℃ and keep it stable for 10min, weigh 0.17612g of ascorbic acid and completely dissolve it in 10mL of distilled water, drop it into the above three-necked flask stabilized at 80℃, stir it for 2h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nanofluorescent and nanopalladium composite material MOF material precipitate.

[0042] NaYF4:Yb 3+ / Er 3+ -TEM and EDS detection and analysis of MOF samples

[0043] By detecting NaYF4:Yb 3+ / Er 3+ -MOF material samples to obtain their TEM Figure 1-a, 1-b, 1-c, observing the transmission electron microscopy images of the samples, it can be seen that the samples present a typical core-shell structure and a uniform lattice structure. The sample morphology at a low magnification of 50nm is as follows Figure 1 -c has good uniformity, and the average size is maintained at about 150nm, which is manifested by the uniformity of MOF material coating upconversion fluorescent nanomaterials and Pd / NaYF4:Yb 3+ / Er 3+ -MOF materials are mostly shaped like standard prisms. The morphology of samples at high magnification and 5nm scale is as follows: Figure 3 a shows that the crystal has a more obvious striped lattice distribution.

[0044] Each element has its own characteristic X-ray wavelength, the size of which is determined by the characteristic energy released by each element during energy level transition. The elements in the sample can be detected by an X-ray energy spectrometer (EDS). Figure 2 NaYF4:Yb 3+ / Er 3+ -X-ray spectrum of MOF materials. It can be seen from the figure that the samples have different contents of elements Yb, Y, Er and a large amount of element Zn. Zn exists in the sample as a metal organic framework material element, and Yb, Y, Er are wrapped in it as up-conversion fluorescent material elements. Preliminary judgment proves that NaYF4:Yb is successfully synthesized. 3+ / Er 3+ -MOF materials.

[0045] Pb / NaYF4:Yb 3+ / Er 3+ -TEM and EDS detection and analysis of MOF samples

[0046] Synthesis in water

[0047] like Figure 3 Pd / NaYF4:Yb synthesized in water 3+ / Er 3+ -TEM of MOF material samples Figure 3 -a, 3-b, and 3-c show obvious core-shell structures under high magnification, and the morphology is octahedral. Under low magnification, they show a relatively messy coating morphology, which is not uniform and irregular. There are only a few suitable morphologies such as Figure 3 -b, not representative. After consulting the literature and analyzing, it is speculated that some materials or organic frameworks are dissolved in the water phase during the synthesis process. Experimental verification shows that the MOF synthesized in the water phase is flaky. Therefore, the Pd / NaYF4:Yb synthesized in the water phase did not obtain uniformly coated and regular morphology. 3+ / Er 3+-MOF materials, methanol was used as solvent to further explore the synthesis experiments, so the materials synthesized in water phase were no longer tested as samples.

[0048] Synthesis in methanol system

[0049] like Figure 4 As shown, Figure 4 -a, 4-b, and 4-c are Pd / NaYF4:Yb synthesized in methanol phase. 3+ / Er 3+ -TEM image of a MOF material sample, which was prepared by solvothermal method in NaYF4:Yb 3+ / Er 3+ -MOF material, the rare metal element Pd, which plays a role in photothermal conversion and catalysis, is encapsulated into the pores of the metal organic framework shell. The TEM image at a high magnification microscope at a 5nm scale is shown below: Figure 4 -a, the sample crystal not only shows obvious striped lattice distribution, but also compares with NaYF4:Yb 3 + / Er 3+ -TEM images of MOF material samples Figure 1 -a, in this image, there are a lot of black dots at the scale of 2-5nm, which are evenly dispersed without obvious agglomeration, which is consistent with the description of the particle size distribution of palladium element and should have high reactivity. Figure 5 The presence of Pd in ​​the crystal also shows that the rare metal element palladium has been successfully coated. The TEM image at a low magnification of 200nm is shown in the figure. Figure 4 -c, the material sample has a relatively regular morphology and is evenly coated, compared with NaYF4:Yb 3+ / Er 3+ -TEM images of MOF material samples Figure 1 -c, not much has changed.

[0050] Element distribution and analysis

[0051] To illustrate the final synthesized sample Pd / NaYF4:Yb 3+ / Er 3+ -MOF material is based on the fluorescent material NaYF4:Yb 3+ / Er 3+ As the core, the organic framework structure with zinc as the metal source is a typical ZIF-8 core-shell structure. Figure 6 It can be seen that the particle size distribution of the sample is around 150nm. The EDS element distribution test of the sample is as follows Figure 7From the EDS element distribution diagram, it can be seen that the Y, Yb, and Er elements are mainly concentrated in the core, indicating that the core is an up-conversion fluorescent material. The Zn element is densely distributed in various parts of the crystal, obviously serving as a framework to support the crystal. It shows that the Pd element is also widely present in various parts of the crystal, which is relatively sparse compared with Zn, indicating that the palladium element is evenly distributed in the pores of the metal organic framework.

[0052] To further illustrate that the synthesized product is Pd / NaYF4:Yb 3+ / Er 3+ -MOF materials, the element proportions of the samples are detected as shown in Table 1. It can be clearly seen from the table that the elements Y, Yb, Er, and Pd exist in the samples at different contents, which shows that the metal organic framework is coated with NaYF4:Yb 3+ / Er 3+ and Pd element, which clearly shows that the ideal Pd / NaYF4:Yb 3+ / Er 3+ -MOF materials.

[0053] Table 1 Element distribution diagram Total number spectrum

[0054]

[0055]

[0056] Fluorescence spectroscopy analysis

[0057] Figure 8 NaYF4:Yb 3+ / Er 3+ -MOF, Fig. 9 Pd / NaYF4:Yb 3+ / Er 3+ -MOF fluorescence spectrum under external 980nm excitation light source. It can be seen from the figure that both samples have peaks at around 550nm, 650nm and 668nm, showing green and red light. Although there are some differences, they are generally similar. It can be considered that the incorporation of nano-palladium has little effect on the fluorescence characteristics of up-conversion fluorescence. The peaks of both samples are derived from Yb 3+ -Er 3+ Characteristic emission, occurs between ions 2 F 7 / 2 - 2 F 5 / 2 (Yb 3+ ), 4 I 15 / 2 - 4 I 12 / 2 (Er 3+ ), 4 I 15 / 2 -4 I 12 / 2 (Er 3+ ) a series of energy transfer and energy level transition, and finally 2 F 7 / 2 Electrons jump to lower energy levels 2 H 11 / 2 , 4 S 3 / 2 and 4 F 9 / 2 The energy level or returns to the ground state in the form of radiated photons, thereby emitting green and red light with wavelengths of 550, 650 and 668nm.

[0058] 5X-ray diffraction detection

[0059] use Fig.10 The XRD spectrum in the sample determines the crystal structure, composition and internal atomic arrangement of the sample. Fig.10 It can be clearly seen that in addition to the characteristic peaks of upconversion fluorescent materials and nano-palladium in the XRD spectrum of the sample, six characteristic peaks belonging to the (114), (233), (134), (044), and (244) crystal planes of ZIF-8 crystal appear at diffraction 2θ angles of 10.4°, 12.7°, 14.6°, 16.3°, and 18.1°, which are roughly the same as the crystal data given in the literature. Combined with the above TEM image and fluorescence spectrum, the sample belongs to a hexagonal phase structure and has a good crystal structure. The peak value and peak range of the characteristic peaks correspond well, indicating that the addition of upconversion fluorescent materials and nano-palladium has not changed the basic framework of ZIF-8, indicating that the sample still has good stability, and Pd / NaYF4:Yb with high crystal purity and good crystallinity has been successfully synthesized. 3+ / Er 3+ -MOF.

[0060] In summary, by combining nano-Pd with NaYF4:Yb 3+ / Er 3+ Pd / NaYF4:Yb is doped into the zeolite imidazole framework ZIF-8 to obtain a stable composite of the two materials. 3+ / Er 3+ -MOF, two different materials with different properties are doped into the same system at the same time, breaking through the limitations of single material composite, providing the possibility of realizing the simultaneous composite of three or more materials, and using TEM, EDS, XRD fluorescence spectroscopy and other means to characterize the samples with good properties. Combined with the characteristics of nanopalladium and upconversion fluorescent materials in the literature, it can provide possibilities for applications in catalysis, fluorescence, degradation, photothermal conversion, etc.

[0061] Although the present invention has been described above with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed by the present invention may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A Pd@NaYF4Yb 3+ Er 3+ @The preparation method of MOF composite material is characterized by: The Pd@NaYF4Yb 3+ Er 3+ The preparation method of the MOF composite material comprises the following steps: S1: Synthesis of upconversion nano fluorescent materials: weigh 0.473g of analytically pure yttrium chloride hexahydrate, 0.155g of ytterbium chloride hexahydrate, and 0.0153g of erbium chloride hexahydrate one by one and place them in a 50mL beaker, measure 10mL of ethylene glycol and pour it into the above beaker, stir with a glass rod to dissolve, weigh 0.5g of xylitol and add it to dissolve, and assist in accelerating in a heating mantle until all the drugs are dissolved, weigh 0.168g of sodium fluoride and dissolve it in 10mL of ethylene glycol and place it in a 25mL beaker, stir with a glass rod until it is completely dissolved, and then add it dropwise to the above 50mL beaker, then pour all the solution into a high-pressure reactor and place it in a muffle furnace under constant temperature conditions, let it stand for a period of time, cool it naturally, and then take it out, centrifuge the solution at high speed and pour out the supernatant, retain the bottom upconversion nano fluorescent material precipitate for standby use; S2: Synthesis of upconversion nano fluorescent composite material MOF: Weigh 0.0792g polyvinyl pyrrolidone and completely dissolve it in 10mL methanol, and place it in a sealed plastic bottle. Take the upconversion fluorescent material in step S1 and wash it twice with methanol to wash away the excess reactants, pour it into a plastic bottle, seal it, and stir it for 12h at room temperature as solution C for standby use. Weigh 0.6568g analytical pure 2-methylimidazole and completely dissolve it in 9mL methanol, and place it in a 25mL beaker as solution A for standby use. Weigh 0.2916g zinc nitrate and completely dissolve it in 9mL methanol, and place it in a 50mL beaker as solution B for standby use. Pour solution C into solution B and mix well, place solutions A and B in a refrigerator for 15 minutes and then take them out, pour solution A into solution B and mix well, then refrigerate in an ice bath at 0°C for 24 hours, take them out and centrifuge them at 12000r / min for 15 minutes, pour out the supernatant, and keep the bottom upconversion nano fluorescent composite material MOF material precipitate for later use; S3: Synthesis of upconversion nanofluorescent and nano-palladium composite MOF: Synthesis of upconversion nanofluorescent and nano-palladium composite MOF is synthesized by methanol system or by water system The methanol system synthesis includes the following steps Weigh 0.01g of potassium chloropalladate, stir thoroughly and completely dissolve in 30mL of methanol, and place in a sealed plastic bottle. Take the upconversion fluorescent composite material MOF in the previous step and wash it twice with methanol to wash away excess reactants, pour it into the methanol solution of potassium chloropalladate, seal it, stir it at room temperature for 24h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom precipitate for later use. Weigh 0.01g of sodium borohydride and dissolve it in 10mL of methanol at 0℃ and place it in a sealed plastic bottle for later use. Wash the bottom precipitate with methanol three times, ultrasonically disperse it into 10mL of methanol, and then drop it into the methanol solution of sodium borohydride drop by drop, seal it, stir it at room temperature for 2h, take it out and centrifuge it at 6000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nano-fluorescence and nano-palladium composite material MOF material precipitate; The water system synthesis includes the following steps Weigh 0.0326g of potassium chloropalladate and completely dissolve it in 10mL of distilled water, place it in a sealed plastic bottle, take the upconversion fluorescent composite material MOF in the previous step, wash it twice with distilled water to wash away excess reactants, pour it into the aqueous solution of potassium chloropalladate, seal it, stir it at room temperature for 12h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, retain the bottom precipitate, disperse it in 10mL of distilled water, place it in a 100mL three-necked flask, oil bath it at 80℃ and keep it stable for 10min, weigh 0.17612g of ascorbic acid and completely dissolve it in 10mL of distilled water, drop it into the above three-necked flask stabilized at 80℃, stir it for 2h, take it out and centrifuge it at 8000r / min for 10min, pour out the supernatant, and retain the bottom upconversion nanofluorescent and nanopalladium composite material MOF material precipitate.

2. A Pd@NaYF4Yb according to claim 1 3+ Er 3+ @The preparation method of MOF composite material is characterized by: The temperature of the heating jacket in step S1 is 80°C.

3. A Pd@NaYF4Yb according to claim 2 3+ Er 3+ @The preparation method of MOF composite material is characterized by: The constant temperature in step S1 is 200°C.

4. A Pd@NaYF4Yb according to claim 3 3+ Er 3+ @The preparation method of MOF composite material is characterized by: In step S1, the solution is allowed to stand in a muffle furnace for 2 hours.

5. A Pd@NaYF4Yb according to claim 4 3+ Er 3+ @The preparation method of MOF composite material is characterized by: The centrifugal speed of the solution in step S1 is 12000 r / min, and the centrifugal time is 15 min.

6. A Pd@NaYF4Yb according to claim 5 3+ Er 3+ @The preparation method of MOF composite material is characterized by: The A and B solutions in step S2 are placed in a refrigerator at 0°C.

Citation Information

Cited By

  • Bionic self-repairing photo-thermal stable SBS-CR composite modified asphalt and preparation method thereof

    CN121379186A